1987
DOI: 10.1073/pnas.84.7.1945
|View full text |Cite
|
Sign up to set email alerts
|

Final steps in exocytosis observed in a cell with giant secretory granules.

Abstract: Secretion by single mast cells was studied in normal and beige mice, a mutant with grossly enlarged secretory vesicles or granules. During degranulation, the membrane capacitance increased in steps, as single secretory vesicles fused with the cell membrane. The average step size was 10 times larger in beige than in normal mice, in agreement with the different granule sizes measured microscopically in the two preparations. Following individual capacitance steps in beige mice, individual granules of the appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
147
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(151 citation statements)
references
References 21 publications
4
147
0
Order By: Relevance
“…3b, 4). If L-DOPA stimulates exocytosis, then it is possible that the increase in vesicle volume that is observed after treatment with L-DOPA could result from the influx of extracellular solution into the vesicles during membrane fusion (Breckenridge and Almers, 1987;Zimmerberg et al, 1987). However, on the basis of the morphological criteria used in previous studies of PC12 cells, all vesicle measurements were felt to reflect the morphology of dense core vesicles that were not actively involved in exocytosis (Watanabe et al, 1983;Madeddu et al, 1985;Hase et al, 1996).…”
Section: Effects Of L-dopa and Reserpine On Quantal Size And Vesiculamentioning
confidence: 93%
“…3b, 4). If L-DOPA stimulates exocytosis, then it is possible that the increase in vesicle volume that is observed after treatment with L-DOPA could result from the influx of extracellular solution into the vesicles during membrane fusion (Breckenridge and Almers, 1987;Zimmerberg et al, 1987). However, on the basis of the morphological criteria used in previous studies of PC12 cells, all vesicle measurements were felt to reflect the morphology of dense core vesicles that were not actively involved in exocytosis (Watanabe et al, 1983;Madeddu et al, 1985;Hase et al, 1996).…”
Section: Effects Of L-dopa and Reserpine On Quantal Size And Vesiculamentioning
confidence: 93%
“…During cell secretion, the fusion pore either irreversibly expands or closes [24,[29][30][31]. The latter process, where the fusion pore opens allowing secretory vesicles to fuse momentarily and subsequently close, has been referred to as 'transient fusion' [24,26,30,31]. Experimental data from these and other studies, and from theoretical considerations, gave rise to a hypothetical working model of the exocytotic fusion pore [29,32] in cells.…”
Section: Porosome: the Universal Secretion Machinerymentioning
confidence: 99%
“…Electrophysiological measurements of mast cells [23][24][25][26][27] as well as adrenal chromaffin cells [28], suggested the presence of fusion pores at the cell plasma membrane as "dynamic entities", originating following a secretory stimulus [29]. Results from earlier studies on cell capacitance and conductance measurements, suggested that following stimulation of secretion, the "exocytotic fusion pore" abruptly appears as a 1-2 nm in diameter pore at the cell plasma membrane, with conductance similar to a large ion channel [29].…”
Section: Porosome: the Universal Secretion Machinerymentioning
confidence: 99%
See 1 more Smart Citation
“…They may be due to the fusion of granules, which are too small to be resolved as stepwise changes by this method. Alternatively, these apparently continuous changes could also be a consequence of an initial flickering of the fusion pores (8). Flickering of the fusion pore which is faster than the time resolution of the measurement will lead to an apparent capacitance value between the unfused and fused state, corresponding to the time average of the fusion pore to be in the open or closed state, respectively.…”
Section: High Resolution Measurements Reveal Discrete Fusion Eventsmentioning
confidence: 99%